Pengaruh Gaya Kepemimpinan Transformasional, Komitmen Organisasi dan Keterikatan Karyawan Terhadap Produktivitas Kerja di CV Analisa Wijaya Group Yogyakarta - Shofiyana Kusuma Astuti (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
This study Sims to determine whether the Transformasional Leadership Style, Organizational Commitment, and Employee Engagement affect Work Productivity. This research method used quantitative descriptive method using a questionnaire. This study took a sample of 45 respondents who were still working until the end of 2019. The sampling technique wae probability sampling using the simple random sampling method. By giving questionnaires to respondents without seeing the age limit as many samples as needed. The results shower that the Transformational Leadership Style and Employee Engagement had a significant positive effect on Work Productivity. While Organizational Commitment has no effect on Work Productivity. But simultaneously all X variables affect the Y variable.